KAJIAN POTENSI PEMANFAATAN BIOGAS SEBAGAI SALAH SATU SUMBER ENERGI ALTERNATIF DI WILAYAH MAGELANG - Rany Puspita Dewi (Universitas Tidar, 2018)
The increasing consumption of fossil-based energy especially LPG (Liquid Petroleum Gas) that is not balanced with the availability of energy source, required a development of alternative energy with abundant amount and environmentally friendly. One of alternative energy source feasible to develop is the one from biomass waste that is livestock manure. Magelang becomes one of potential area in Central Jawa as biogas development. Biogas is produced by using digester anaerobically. Magelang has livestock about 142.127 with potency of gas production about 86.690 m3. The resulted biogas production equals to 43.345 kg of LPG or 14.448 of LPG 3 kg which is can fullfill the cooking needs for about 278 households in one year.Keywords: biogas, energy, LPG